In Vitro Studies on Effect of Endophytic Bacteria and Rhizobium on Seed Quality Parameters in Chickpea - HARISHKUMAR LAXMAN KANABUR; ASHOK S SAJJAN; GP SANTHOSH (Seed Research, 2026)
Endophytes are microorganisms that reside in the tissues of living plants are relatively unstudied asa potential source of novel natural products for exploitation in medicine, agriculture and industry. In present study,the endophytes were extracted from aerial parts of chickpea (stem and leaves) brought from three different villagesof Vijayapur district. The isolation of bacteria was done and their morphological and biochemical properties werestudied. The screening was done to select efficient endophytes based on compatibility test between RhizobiumGV-2 and the isolated endophytic bacteria and indole acetic acid test. Accordingly, three efficient endophytes BL4, MS-1 and MS-4 were selected and identified as Bacillus thuringiensis, B. cereus strain LPDB2 and B. cereusstrain LPDB5 based on 16S rRNA molecular identification. These three efficient endophytes along with theRhizobium GV-2 were treated with the chickpea seeds in different combinations. The investigation has aimed inseed quality parameters under in vitro condition. Seed quality parameters include seed germination percentage,seedling length, seedling vigour index-I and test weight. The significant difference was observed among thetreatments and the results revealed that treatment with B. thuringiensis + B. cereus strain LPDB2 + B. cereusstrain LPDB5 + Rhizobium GV-2 noticed significantly higher performance in seed quality parameters.